Fabrication of high-performance symmetric supercapacitor of graphene electrodes by tuning their electrochemical properties. (10th December 2022) - Rajeevan, Sreelakshmi; John, Sam; Ponnamma, Deepalekshmi; George, Soney C.
Abstract: The electrochemical efficiency of a supercapacitor highly depends on the electrochemical properties of electrodes used in its fabrication. Herein, we synthesize highly efficient reduced graphene oxide (rGO) electrodes by tuning the concentration of polyvinylidene fluoride (PVDF) as a binder through solvent evaporation. The structural, morphological, and electrochemical properties of rGO/PVDF composite electrodes are characterized using Fourier transform infrared spectroscopy (FTIR), X-ray powder diffraction (XRD), Raman spectroscopy, Scanning electron microscopy (SEM), and Transmission scanning electron microscopy (TEM), Cyclic voltammetry (CV), Galvanostatic charge-discharge analysis (GCD), and Electrochemical impedance spectroscopy (EIS). The rGO/PVDF composite electrodes possess an elliptical-shaped voltammogram with high symmetry, and quasi-triangular-shaped GCD curves indicating the ideal supercapacitor characteristic with excellent charging-discharging stability. The highest specific capacitance of 307 F/g at a scan rate of 100 mV/s and 1080 F/g at a current of 0.1 mA was obtained for the PvG2 electrode. The symmetric electrical double layer (EDLC) supercapacitor fabricated using the PvG2 electrode has an elliptical-shaped voltammogram with high symmetry, which indicates ideal supercapacitor behaviour. The highest power and energy densities gained for the supercapacitors are 2400 W/Kg and 24.1 Wh/Kg at 0.02A and 0.003 A respectively. Furthermore, approximately 78.9 % of capacitance retention and 91.03 % coulombic efficiency were observed for supercapacitors after 5000 cycles. Graphical abstract: Unlabelled Image Highlights: High electrochemically performing rGO/PVDF composite electrodes are synthesized by solvent evaporation. rGO/PVDF electrodes with lower binder content i.e., PvG2 electrode showed excellent electrochemical properties. The specific capacitance for the PvG2 electrode is 307 F/g and 1080 F/g from the CV and GCD analysis respectively Fabricated supercapacitor exhibits the highest power and energy densities of 2400 W/Kg and 24.1 Wh/Kg at 0.02 A and 0.003 A respectively. Capacitance retention of 78.9 % and coulombic efficiency of 91.03 % are gained for the supercapacitor after 5000 cycles.